Strategi Antisipasi Bencana Alam untuk Meningkatkan Kesiapsiagaan Masyarakat - Burhan Zahadi; Hasan Zakki (Lembaga Publikasi Ilmiah Nusantara, 2026)
Indonesia is a country with a high level of vulnerability to natural disasters, such as earthquakes, floods, landslides, and volcanic eruptions. This condition demands high community preparedness to minimize the risk of casualties and material losses. This community service activity aims to enhance community preparedness through the implementation of structured and sustainable natural disaster anticipation strategies. The methods used include disaster socialization, mitigation training, emergency response simulations, and the development of community-based evacuation plans. The target participants are residents in disaster-prone areas who have limited access to disaster-related information and knowledge. The results of the activity indicate an improvement in community understanding regarding types of natural disasters, early warning signs, and the necessary steps to take before, during, and after a disaster occurs. Furthermore, the community has become better prepared for emergency situations, as evidenced by increased active participation in simulations and the ability to formulate independent evacuation plans. This initiative also encouraged the formation of local disaster-preparedness groups to ensure program sustainability. Thus, natural disaster anticipation strategies using educational and participatory approaches have proven effective in increasing community preparedness. It is hoped that similar programs can be widely implemented to strengthen community resilience against natural disasters.